Determination of factors influencing the degree of reduction disintegration in Northern Cape lump ore and the role of gangue minerals in the propagation of cracks - Pistorius, Petrus Christiaan (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.